Epidemiological and clinical characteristics of the largest COVID-19 outbreak along the China-Myanmar border in Ruili City, Yunnan Province, China - Yan, Xiangyu; Hao, Linhui; Wang, Zekun; Wang, Xuechun; Zhang, Xiangyu; Li, Tao; Jia, Zhongwei; Chang, Litao; Zhang, Bo; Shui, Tiejun (Frontiers in Public Health, 2022)
Background Imported COVID-19 patients posed great challenges to border areas' COVID-19 control. However, research was scarce to reveal epidemiological characteristics of COVID-19 in border areas. This study aimed to explore the detailed transmission chains, and reveal epidemiological and clinical characteristics of the largest COVID-19 outbreak caused by Delta variant of concern (VOC) occurred in the China-Myanmar border area. Methods During the outbreak from July to September, 2021 in Ruili City, Yunnan Province, China, epidemiological investigation data and clinical-related data pertaining to confirmed COVID-19 patients were collected. Patients' contact history data and viral gene sequencing were used for inference of transmission chains. Sociodemographic and epidemiological characteristics, cycle threshold (Ct) value, and antibodies level were compared between patients who were vaccinated against COVID-19 or not. Results A total of 117 COVID-19 patients were confirmed during the outbreak, among which 86 (73.5%) were breakthrough infections. These patients evenly split between Chinese and Myanmar people (50.4% vs. 49.6%). Most of these patients were mild (45.3%) or moderate (48.7%) infections with no death reported. Multi-source of infection led to 16 transmission chains with a maximum of 45 patients in one chain. Patients vaccinated against COVID-19 before infection had relatively higher antibodies (IgM and IgG) levels and more rapid response to infection than non-vaccinated patients (p < 0.05). Conclusion Land border areas have greater risks of imported COVID-19 and more complicated epidemics. It should be cautious in formulating entry and exit requirements for border areas. The immune effect of COVID-19 vaccines and related mechanism should be further explored.